Employees’ health related quality of life in medical education provider setting: Does academicians report higher scores? - Suzana Suddin, Leny; ., . (International Journal of Engineering and Technology, 2018)
Purpose: The objective of this study was to measure level of health-related quality of life among employees working in medical education providerâ€™s setting and its association with type of jobs as academicians or non-academicians. Approach: A cross sectional study was conducted among employees in a medical education providerâ€™s setting. Study instrument consisted of validated Medical Outcome 36-item Short Form Survey (MOS-36) questionnaire were distributed as online survey form. All employees in the study location were recruited. Significant difference in quality of life scores were compared between job types using chi square and Mann-U Whitney statistical test. Results: A total of 196 employees participated in this study. Majority of them were female employees (59%) with Master degree level of education (20%). Academicians were found to score higher in 6 out of 8 domains measured compared to non-academicians. Significant associations were observed between these 2 groups involving 3 domains which were physical functioning (Difference in scores= 10.0, U=2589, p=0.01), emotional health (Difference in scores= 12.0, U=2496, p=0.01) and general health (Difference in scores=10.0, U=2452, p=0.004) domains. Findings from this study supported existing evidence in literature which revealed that in general, academicians did have higher level of HRQOL when compared with their counterparts. These findings would add to existing but limited knowledge on the HRQOL status of healthy working population; because in the past, majority of previous HRQOL studies were emphasized towards patientsâ€™ population or population with special conditions. Conclusion: Future initiatives or strategies by policy makers and employers for ensuring good HRQOL among this healthy working population should focus on improving general, physical and emotional health of their employees.Â